Henry Van de Velde awards & labels 2011 : loopbaan - bedrijf - jong talent - ovam ecodesign PRO - publiek 2010. - Van Roy, Mies; Cleeren, Steven; Geusens, Miranda; Oosterlinck, Christian; Valcke, Johan (Brussel : Design Vlaanderen, 2012)
Lachaert, Sofie ; Buzzispace ; De Bondt, Sara ; hegge ID ; Van Hulle, Raf ; Hamacher, Kaspar ; Arnout, Klaas ; Maes, Sandra ; GBO Design ; Vervaeke, Christophe ; Gilles, Alain ; Couvreur & Devos ; Enthoven Associates ; Dirk Wynants (dw²) ; Charles, Raphaël (Raphaël Charles Studio)
Henry Van de Velde Awards & Labels 2011 en de OVAM Ecodesign Award PRO 2011, Vlaams Parlement, De Loketten, Brussel, 18 januari 2012 t/m 25 februari 2012
boek